MEMBANGUN KOMUNIKASI IMAN DAN PELAYANAN KARYA MISIONER GEREJA DI TENGAH KELUARGA - Ola Rongan Wilhemus (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Modern communication medium allows one to easily share stories, establish contact with family members, to thank and apologize. Aware of the benefits of this communication medium each family member should utilize communications media wisely and more humanely. In the midst of this communication medium advancement of Christ's faithful should regard the family as a school of faith and a special communication experience divine grace. Each family who live karinia Divine love is called to give concrete testimony of the love of it. Every Christian family is a concrete sign of the presence and implementation of the tasks of the Church that lives. When carrying out this missionary task, God is always present in the family to bless, sanctify and strengthen family members. The presence of God is happening in real time when families gather to pray, worship and hear God's word together.